Effect of flow field geometry on hydrodynamics of flow in redox flow battery - Kumar, M. Narendra; Kumar, S. Manoj; Vijayakumar, G. C.; Kadirgama, Kumaran; Samykano, Mahendran; Venkatesh, Krishna; Murlidhara, H. B. (Tech Science Press, 2022)
This study computationally investigates the hydrodynamics of different serpentine flow field designs for redox flow batteries, which considers the Poiseuille flow in the flow channel and the Darcy flow porous substrate. Computational Fluid Dynamics (CFD) results of the in-house developed code based on Finite Volume Method (FVM) for conventional serpentine flow field (CSFF) agreed well with those obtained via experiment. The deviation for pressure drop was less than 5.1% for all the flow rates, thus proving the present CFD analysis’s validity on the modified variation of serpentine flow fields. Modified serpentine flow field-2 (MSFF2) design provided least pressure drop across the channel and maximum velocity penetration across the porous substrate when compared to the other designs. This increases its wetting ability, which is very important in terms of mass transfer over potential for electrochemical reaction happening in the porous substrate to achieve effective electrochemical cell performance.